2020
DOI: 10.1055/a-1164-6282
|View full text |Cite
|
Sign up to set email alerts
|

EUS-directed transgastric endoscopic retrograde cholangiopancreatography versus laparoscopic-assisted ERCP versus deep enteroscopy-assisted ERCP for patients with RYGB

Abstract: Background and study aims Endoscopic ultrasound-directed transgastric endoscopic retrograde cholangiopancreatography (ERCP) (EDGE) is a novel technique for managing pancreaticobiliary diseases in patients with a history of Roux-en-Y Gastric Bypass (RYGB). It has shown to have high technical success rates and fewer adverse events as compared to laparoscopic-assisted ERCP (LA-ERCP). We compared the technical success and clinical outcomes of EDGE vs. LA-ERCP vs. E-ERCP. Patients and methods A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 13 publications
0
51
0
Order By: Relevance
“…A detailed report of the abstract review and full text review is described in Figure 2. The included studies were retrospective cohort studies (n=9) and case reports (n=8) [ Figure 2] [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Study Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed report of the abstract review and full text review is described in Figure 2. The included studies were retrospective cohort studies (n=9) and case reports (n=8) [ Figure 2] [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Study Identificationmentioning
confidence: 99%
“…A total of 2143 abstracts were identified from the initial search of the three databases during the target time period, with 17 articles selected for the final study [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A detailed report of the abstract and full-text reviews is shown in ▶ Fig.…”
Section: Study Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective multicenter review[ 47 ] of 178 patients reported a technical success of 98% (175/178) countered by 4 severe adverse events (SAE) (2.2%) and 10% of patients having a documented persistent fistula (9/90). It has been proposed that the EDGE could be used in patients with a RYGB, of which the details like limb length are unknown, and in patients with a surgically absent gallbladder[ 48 ]. A meta-analysis showed comparable rates of success to the laparoscopic assisted ERCP[ 45 ].…”
Section: Cannulation Biliary Access and Altered Anatomymentioning
confidence: 99%
“…The series by Kochar et al in this edition of EIO [5] is a welcome addition to the existing literature. They present a 56-patient, single-center, 4-year retrospective experience with all three methods, with 26, 18, and 12 patients handled by EDGE, LA-ERCP, and E-ERCP, respectively.…”
mentioning
confidence: 98%